Implementasi Peraturan Pemerintah Nomor 21 Tahun 2008 Tentang Penyelenggaraan Penanggulangan Bencana di Kecamatan Sumur - Cahyo Edi Asmoro (Epistemik: Indonesian Journal of Social and Political Science, 2021)
The post-disaster reconstruction program policy is very important to pay attention to especially in areas that are prone to disasters such as the one in Sumur Subdistrict. The existence of a reconstruction program, so that people, especially those directly affected by disasters, are able to restore the environmental conditions that support people's lives, such as the economic and social conditions they were in the past. Through this reconstruction program policy, the Pandeglang Regency government conducted reconstruction in Sumur Subdistrict, which became the locus of research. The purpose of this research is to find out how the post-disaster reconstruction in Sumur Subdistrict. Researchers use qualitative methods. The selection of informant researchers used purposive sampling and snowball techniques. This study uses the theory put forward by Van Metter and Van Horn consisting of 6 aspects, namely the Purpose and Size of the Policy, Resources, Characteristics of Implementing Agencies, Attitudes and Dispositions of implementing implementors, Communication between implementers, Communication between implementers, Economic, social and political environment . The results of this study indicate that the reconstruction in Sumur Sub-district has not been effective in the communication sector between the government and the community because in the implementation of this policy not many people were involved as the subjects of their programs so that there were many misunderstandings which became obstacles in the implementation of the program.